55‐2: Methods for Overcoming the Trade‐off between Efficiency and Lifetime of Organic Light‐Emitting Diodes: OLED Lifetime Simulation. Issue 1 (25th September 2020) - Lee, Junyoung; Han, Mira; Song, Woojin; Choi, Kyungbok; Cho, Hyunguk; Kim, Yongjo
Abstract : Next generation OLED displays demand high energy efficiency and high resolution, but it is a hard challenge for the OLED display industry to meet the needs for high efficiency and long lifetime simultaneously. When excitons relax to their ground state a photon is emitted; however, such excited exciton states can, on occasion, quench, leading to material degradation. In order to increase efficiency, a high concentration of excitons is needed, but this leads to more quenching events between excitons and polarons and, in turn, increased material degradation. Thus, a trade‐off exists between efficiency and lifetime, which can be alleviated by carefully optimizing the concentration and spatial distribution of excitons. In this paper, we introduce an OLED lifetime model, which we apply to overcome the aforementioned trade‐off. In order to develop the model, we first identified the key quenching factors that dominate efficiency and lifetime degradation. Based on these factors, our model can quantitatively predict device degradation. Subsequently, we can optimize the OLED stack, in terms of layer materials and thicknesses, so as to maximize efficiency, while minimizing degradation. Consequently, we demonstrate an optimized device that exhibits a 6% higher efficiency and a 2.7 times extended lifetime relative to the reference device.